In Search of Zorba – Part II Myths, Realities, and Assorted Bedtime Stories about Leading Open, Online and Distance Education: Myths, Realities, and Assorted Bedtime Stories about Leading Open, Online and Distance Education - Olcott, Jr., Don (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2025)
This paper explores the complexities and challenges of leadership in open, online, and distance education (ODL). It aims to differentiate myths from reality and provide insights into effective leadership practices. Despite extensive scholarly literature and practical experiences, effective leadership remains elusive and difficult to define. The paper presents a view of selected leadership issues, offering a synthesis of innovative practices and experiences. It identifies myths such as the consistency of visionary leadership styles, the effectiveness of leading from the back, and the equivalence of leadership and management. The realities highlight the need for adaptability, front-line leadership, and the distinct roles of leaders and managers. The paper also discusses the limitations of theoretical frameworks, the importance of experience over talent and training, and the challenges of decision-making and embracing change. Through a series of research questions, the paper seeks to provide new vantage points for future empirical research in the field of leadership in ODL.